Processing Leaf Waste Into Compost Using Rice Water And Em4 Fermentation Activators - Ira Suharwati, Sri; Ghafur, Fadolul (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
The purpose of this study was to see the difference in the results of processing leaf waste into compost using different activators between rice water fermentation and EM4. Leaf waste is a concern and problem at Mambaul Ulum Bata-bata Boarding School. The amount of waste that is not processed affects the condition of environmental sustainability. Given the lack of processing of leaf waste that exists to date, it is very important to improve leaf waste management techniques so that the composting process can turn it into a valuable product. This research uses qualitative methods and primary data collection by observation and secondary data by literature study. This research is also experimental to determine the physical changes of compost with the addition of rice water fermentation activator and EM4 liquid. In the results of samples using rice water fermentation activator, the results were obtained with temperatures ranging from 29 - 31 degrees Celsius, dry humidity conditions and pH ranging from 5.7 - 6 which means that some compost is still acidic because it has a pH less than 6. The physical properties of the soil have the characteristics of smelling soil, black in colour, and fungus has spread. As for the results of the second sample using EM4 activator with temperature results ranging from 30 - 32 degrees Celsius, dry humidity conditions and pH ranging from 6.9 - 7.3 which means the compost has a normal pH. The physical properties of the soil have the characteristics of smelling dry leaves, brownish in colour, and white spots appear and begin to spread